The effects of cognitive fatigue on shooting performance in netball - Wong, Li Kai (Nanyang Technological University, 2021)
Netball is a dynamic sport that requires successful goal shooting, to score goals that decides the outcome of the game, but cognitive fatigue can lead to a decline in technical performance. There is a gap in literature on the effects of cognitive fatigue on netball shooting. This study investigates the effects of interventions that induce cognitive fatigue on the shooting performance on elite youth netballer and their performance on an incongruent Stroop Task administered before and after the intervention. The participants were 8 netball athletes aged 14-18 years (mean = 15.9 ± 1.3). This study was a randomised and controlled experimental within-subject investigation, consisting of three visits with a 1-week interval. Female netball athletes participated in three randomised conditions through the three visits: control (CON), mental arithmetic task (MAT) and smartphone usage (SMA). The Stroop Task measured the level of induced cognitive fatigue prior to and after each experimental condition. Subsequently, the athletes completed a shooting task with a total of 45 shots from three angles varying three distances. A statistically significant main effect of pre and post Stroop tasks on the participants completion time was found (F(1, 7) = 8.150, p = .025, ηp2 = .538), however no significant difference was revealed in the shooting performance between at least two of the three conditions (F(2,14) = 1.535, p = .250, ηp2 = .180). In conclusion, the results of this study are inconclusive and require further research to ascertain the effects of cognitive fatigue on goal shooting in netball.